2020
DOI: 10.1074/jbc.ra119.010571
|View full text |Cite
|
Sign up to set email alerts
|

A nicotinamide phosphoribosyltransferase–GAPDH interaction sustains the stress-induced NMN/NAD+ salvage pathway in the nucleus

Abstract: All cells require sustained intracellular energy flux, which is driven by redox chemistry at the subcellular level. NAD+, its phosphorylated variant NAD(P)+, and its reduced forms NAD(P)/NAD(P)H are all redox cofactors with key roles in energy metabolism and are substrates for several NAD-consuming enzymes (e.g. poly(ADP-ribose) polymerases, sirtuins, and others). The nicotinamide salvage pathway, constituted by nicotinamide mononucleotide adenylyltransferase (NMNAT) and nicotinamide phosphoribosyltransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Moreover, NAMPT cytosol/nucleus localization changes according to cell cycle phases: it is excluded from the nucleus immediately after mitosis and it migrates back into it as the cell cycle progresses (111). These data were confirmed also by Grolla et al that demonstrated a transport of NAMPT into the nucleus, GAPDH-mediated, in response to DNA damage (112). On the contrary, the presence of NAMPT in mitochondria remains controversial (30,46,109).…”
Section: Namptmentioning
confidence: 66%
“…Moreover, NAMPT cytosol/nucleus localization changes according to cell cycle phases: it is excluded from the nucleus immediately after mitosis and it migrates back into it as the cell cycle progresses (111). These data were confirmed also by Grolla et al that demonstrated a transport of NAMPT into the nucleus, GAPDH-mediated, in response to DNA damage (112). On the contrary, the presence of NAMPT in mitochondria remains controversial (30,46,109).…”
Section: Namptmentioning
confidence: 66%
“…Indeed, it is now emerging that it is much more than a simple workhorse to replenish NAD. The complexity of this enzyme is exemplified by the fact that, while the role as an extracellular cytokine is yet not fully elucidated, it has just emerged that it can also shuttle to the nucleus in cells to provide NMN/NAD on site (Svoboda et al, 2019;Grolla et al, 2020). Although more information has to be gathered, it is now apparent that the hypothesis of using NAMPT inhibitors as a single agent is possibly flawed by the occurrence of side effects.…”
Section: Resultsmentioning
confidence: 99%
“…NAD levels can therefore restrict the activity of these two classes of NAD-metabolizing enzymes. Intriguingly, NAD can rapidly shuttle between different cellular compartments to reconstitute the pool that allows enzyme activation, as has recently been shown (46). When in the extracellular space, eNAD functions are linked to the modulation of cell surface P2X and P2Y purinergic receptor families, thereby acting in an apparently enzyme-independent way and eliciting pro-inflammatory immune responses (Figure 1).…”
Section: Intracellular and Extracellular Nad-metabolizing Machinerymentioning
confidence: 89%